1989
DOI: 10.1136/jcp.42.8.834
|View full text |Cite
|
Sign up to set email alerts
|

Topographic association between active gastritis and Campylobacter pylori colonisation.

Abstract: SUMMARY One thousand biopsy specimens obtained from 10 sites in the stomachs of 50 patients were examined for the presence of active chronic gastritis and Campylobacter pylori. All 32 patients with active chronic gastritis at 234 out of 320 sites were positive for Cpylori: 227 showed colonisation with Cpylori by the Warthin-Starry stain; and 222 were positive by culture. Cpylori was not found in 18 patients with inactive chronic gastritis or histologically normal mucosa. The area of C pylori colonisation was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(82 citation statements)
references
References 17 publications
0
78
1
3
Order By: Relevance
“…However, the site-dependent colonisation observed was similar to that described for man [34]. It has been reported that differences in distribution relate to differences in local acid output in the H. felis-infected mouse model [35].…”
Section: Discussionmentioning
confidence: 53%
“…However, the site-dependent colonisation observed was similar to that described for man [34]. It has been reported that differences in distribution relate to differences in local acid output in the H. felis-infected mouse model [35].…”
Section: Discussionmentioning
confidence: 53%
“…4: SS1 predominated in antrum mucosal DNA (B), but not among single-colony isolates (A)]. Such differences may stem from use of different halves of the stomach in these two tests and the patchiness of many H. pylori infections (Bayerdorffer et al, 1989;Anonymous, 1986).…”
Section: Strain Distribution Does Not Depend On Order Of Inoculationmentioning
confidence: 99%
“…1 Nevertheless, the sensitivity of biopsy-based tests and culture is significantly influenced by the density, viability and distribution of bacteria in the gastric mucosa. 6 In certain circumstances, e.g. short time after use of antibiotics, recent or ongoing use of proton pump inhibitors (PPI), and in patients with gastric mucosal atrophy, biopsy based methods may fail due to biopsy sampling error.…”
Section: Introductionmentioning
confidence: 99%